Molecular Evolution of the Substrate Utilization Strategies and Putative Virulence Factors in Mosquito-Associated Spiroplasma Species. (17th February 2014) - Chang, Tean-Hsu; Lo, Wen-Sui; Ku, Chuan; Chen, Ling-Ling; Kuo, Chih-Horng
Abstract : Comparative genomics provides a powerful tool to characterize the genetic differences among species that may be linked to their phenotypic variations. In the case of mosquito-associated Spiroplasma species, such approach is useful for the investigation of their differentiations in substrate utilization strategies and putative virulence factors. Among the four species that have been assessed for pathogenicity by artificial infection experiments, Spiroplasma culicicola and S. taiwanense were found to be pathogenic, whereas S. diminutum and S. sabaudiense were not. Intriguingly, based on the species phylogeny, the association with mosquito hosts and the gain or loss of pathogenicity in these species appears to have evolved independently. Through comparison of their complete genome sequences, we identified the genes and pathways that are shared by all or specific to one of these four species. Notably, we found that a glycerol-3-phosphate oxidase gene ( glpO ) is present in S. culicicola and S. taiwanense but not in S. diminutum or S. sabaudiense . Because this gene is involved in the production of reactive oxygen species and has been demonstrated as a major virulence factor in Mycoplasma, this distribution pattern suggests that it may be linked to the observed differences in pathogenicity among these species as well. Moreover, through comparative analysis with other Spiroplasma, Mycoplasma, and Mesoplasma species, we found that the absence of glpO in S. diminutum and S. sabaudiense is best explained by independent losses. Finally, our phylogenetic analyses revealed possible recombination of glpO between distantly related lineages and local rearrangements of adjacent genes.